2008
DOI: 10.1200/jco.2007.14.6597
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Receptor Tyrosine Kinase Profiles Identify Patients With Enhanced Benefit From Anthracyclines in the BR9601 Adjuvant Breast Cancer Chemotherapy Trial

Abstract: Patients with HER2 amplified and those with HER1, HER2 FISH, or HER3-positive tumors did not benefit from the addition of epirubicin to CMF. Conversely, patients with HER2 nonamplified and HER1 through HER3-negative tumors showed significantly increased RFS and OS rates when treated with epi-CMF compared with CMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 33 publications
(4 reference statements)
5
72
0
7
Order By: Relevance
“…Analysis of Chr17CEP duplication in BR9601, NEAT and MA.5 suggests chromosome 17 to be an independent predictive marker of anthracycline sensitivity. Therefore, Chr17CEP duplication provides the first unifying hypothesis of anthracycline response within three trials for which the HER2 data are opposing (Di Leo et al, 2004Leo et al, , 2009Knoop et al, 2005;Pritchard et al, 2006;Reinholz et al, 2007;Bartlett et al, 2008Bartlett et al, , 2009aBartlett et al, , b, 2010. Analysis of Chr17CEP in tumours recruited into the Belgian trial is near completion, which would allow a meta-analysis of chromosome 17 in 2975 patients.…”
Section: Chromosome 17 Centromere Duplicationmentioning
confidence: 99%
“…Analysis of Chr17CEP duplication in BR9601, NEAT and MA.5 suggests chromosome 17 to be an independent predictive marker of anthracycline sensitivity. Therefore, Chr17CEP duplication provides the first unifying hypothesis of anthracycline response within three trials for which the HER2 data are opposing (Di Leo et al, 2004Leo et al, , 2009Knoop et al, 2005;Pritchard et al, 2006;Reinholz et al, 2007;Bartlett et al, 2008Bartlett et al, , 2009aBartlett et al, , b, 2010. Analysis of Chr17CEP in tumours recruited into the Belgian trial is near completion, which would allow a meta-analysis of chromosome 17 in 2975 patients.…”
Section: Chromosome 17 Centromere Duplicationmentioning
confidence: 99%
“…14 Trials have shown that the overexpression, amplification and deletion of topo-IIa does indeed appear to be predictive of anthracycline response 33,34 while others have suggested that the normal expression of Her1 to 3 may be predictive, 35 but whether the true relationship is with HER2 or topo-IIa remains unclear. At this point in time, it appears that the topo-IIa story is not definitive enough to change clinical practice.…”
Section: Predicting Anthracycline Efficacy: Topoisomerase II Alpha (Tmentioning
confidence: 99%
“…First, the molecular differences that exist between breast cancers (Perou et al, 2000;Pollack et al, 2002;Desmedt et al, 2004) support treating different molecular subtypes on the basis of their biology and pathology rather than on pathology alone. Second, clear evidence that molecular subtypes of cancer respond differently to different therapeutic options challenges the 'one size fits all' approach to chemotherapy in cancer (Hayes et al, 2007;Bartlett et al, 2008Bartlett et al, , 2009aBartlett et al, , b, 2010Pritchard et al, 2008;Ellis et al, 2009).…”
mentioning
confidence: 99%